2021
DOI: 10.1080/03043797.2021.1942794
|View full text |Cite
|
Sign up to set email alerts
|

The rapid transition from campus to online teaching – how are students’ perception of learning experiences affected?

Abstract: The COVID-19 pandemic caused a global disruption to higher education, especially in engineering education, where many teaching and learning activities are difficult or impossible to conduct online. This study examines the changes in the students' experiences of this disruption using a 26-item process-oriented course experience questionnaire (CEQ) that was already in use in the Faculty of Engineering at Lund University (LTH), rather than a newly created pandemic questionnaire. This allowed results from spring 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 54 publications
4
44
0
5
Order By: Relevance
“…Regarding cooperation with other students, there was a tendency for association for gender and cooperation, as a larger share of male students (73 %) found that the cooperation with other students was worse when teaching took place online than when it took place on campus as compared to 55% of the female students. The result was marginally significant with a p-value of .072, confirming a trend seen in a previous study of Course Experience Questionnaire results at LTH from spring term in 2020 (Warfvinge et al, 2021). Note: * p-value: .072; student descriptions of their well-being and cooperation with other students were coded as qualitative variables as: Worse = 1, Same/better = 2.…”
Section: Association Between Background Variables and Reports Of Well-being And Cooperationsupporting
confidence: 82%
See 3 more Smart Citations
“…Regarding cooperation with other students, there was a tendency for association for gender and cooperation, as a larger share of male students (73 %) found that the cooperation with other students was worse when teaching took place online than when it took place on campus as compared to 55% of the female students. The result was marginally significant with a p-value of .072, confirming a trend seen in a previous study of Course Experience Questionnaire results at LTH from spring term in 2020 (Warfvinge et al, 2021). Note: * p-value: .072; student descriptions of their well-being and cooperation with other students were coded as qualitative variables as: Worse = 1, Same/better = 2.…”
Section: Association Between Background Variables and Reports Of Well-being And Cooperationsupporting
confidence: 82%
“…Research on effects from the pandemic in a campus environment has shown that students during the pandemic struggled to orient themselves in courses and to find motivation to study (Warfvinge et al, 2021). Such signals surface also in our material.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…On the other hand, students from online courses were more prone to engage in quantitative reasoning. Warfvinge et al [3] point out that Swedish students seem less satisfied and that they receive less feedback from the teachers during the online teaching. Gonzalez et al [4] on the other hand showed in a Spanish study that the students adapted well to the new online learning and increased their study efficiency and that there was a positive effect from the online education on student learning.…”
Section: Introductionmentioning
confidence: 99%